Web Based Payroll Information System Using CodeIgniter at the Regional Secretariat Tasikmalaya Regency - Irawan, Arya Irawan; Komarudin Tasdik (Yayasan Kita Menulis, 2024)
The problem faced in the payroll system at the Regional Secretariat of Tasikmalaya Regency is that the process is still carried out manually or semi-manually, which causes a lack of efficiency and accuracy in payroll management. So it is necessary to develop and implement a web-based Payroll Information System using the CodeIgniter framework to increase efficiency and accuracy in payroll management at the Regional Secretariat of Tasikmalaya Regency. The method used in this research study is software development which includes requirements analysis, design, implementation and system testing. The CodeIgniter framework was chosen because of its advantages in developing fast and structured web applications. This method enables the design and development of an efficient and effective web-based payroll information system. This system is designed to simplify the employee payroll process with features that include managing employee data, position data, attendance, setting salary deductions, payroll and reporting. With this implementation, it is hoped that it can increase efficiency and accuracy in payroll management at the Regional Secretariat of Tasikmalaya Regency.